KARAKTERISTIK KIMIA TEPUNG BIJI KELOR (Moringa oleifera Lam.) DARI BERBAGAI KETINGGIAN TEMPAT TUMBUH - Saadilah, Muh.; Rahmatu, Rostiati; Kadir, Syahraeni (AGROTEKBIS, 2018)
This research aims to obtain the quality of moringa seed with the best chemical characteristics of moringa flour based on the certain growing place altitude of moringa. This research was conducted at Agroindustry Laboratory of Agriculture Faculty, Tadulako University, using Completely Randomized Design (CRD) with one-factor treatment. As the treatment is the growing place altitude of moringa, there were 0-150 m above sea level (asl); 151-300 m asl; 301-450 m asl; and >451 m asl. Each treatment was repeated four times to obtain 16 experimental units. If the treatment is a significant or very significant effect, and then it continued tested by using Honest Significant Difference (HSD) test level of 5% or 1%. The results showed that the best chemical characteristics were found in the protein content in the treatment of 0-150 m asl. that is 41,26%, fat content in the treatment of 151-300 m asl. that is 31,85% and at the treatment of >451 m asl was obtained water content of 7, 94%, fiber content is 32,26% and ash content is 4,59%. Keywords: Altitude growing place, Chemistry and Moringa seed flour